Genotype and allele frequencies of nine STR Loci in Sikhs from Malaysia / Tan Chin Teck - Tan, Chin Teck (2010)
Allele frequencies for nine short tandem repeats (STRs) gene loci (CSF1PO, TPOX,TH01, F13A01, FESFPS, vWA, D16S539, D7S820, D13S317) were obtained from analyses of saliva DNA from 109 unrelated healthy Sikh individuals residing in Malaysia. DNA was extracted using phenol/chloroform/isoamly alcohol method. 2ng of DNA for each sample was amplified following the instruction in GenePrint® STR Systems (Promega Corporation) CTT, FFv and SilverSTR III Multiplex kits. PCR products were separated in denaturing polyacrylamide gel electrophoresis and silver stained using Promega DNA Silver Staining System. The results were then calculated and processed to establish a statistical database for Sikh community. Chi-square test showed agreement in Hardy-Weinberg equilibrium. Average heterozigosity is 85.53.Power of Discrimination is 0.9999999996 and Power of Exclusion is 0.999213. The data was then compared to the reported allele frequencies in the Malay, Chinese and Indian ethnic communities from Malaysia. There is no significant difference in the pattern of distribution of allele frequencies for all the 9 STR among the Sikh community and the other ethnic communities (Malay, Chinese and Indian) in Malaysia